Forecasting the Risk of Brown Tree Snake Dispersal from Guam: a Mixed Transport‐Establishment Model - GAD PERRY; DAN VICE (Conservation Biology, 2009)
The brown tree snake ( Boiga irregularis ) is a devastating invader that has ecologically and economically affected Guam and is poised to disperse further. Interdiction efforts are being conducted on Guam and some of the potential receiving sites, but no tools exist for evaluating the potential for snake incursion; thus, the amount of effort that should be invested in protecting particular sites is unknown. We devised a model that predicts the relative risk of establishment of the brown tree snake (BTS) at a given site. To calculate overall risk, we incorporated in the model information on the likelihood of an organism entering the transportation system, avoiding detection, surviving to arrive at another location, and establishing at the receiving end. On the basis of documented rates of snake arrival at receiving sites, the model produced realistic predictions of invasion risk. Model outputs can thus be used to prioritize interdiction efforts to focus on especially vulnerable receiving locations. We provide examples of the utility of the model in evaluating the impacts of changes in transportation parameters. Finally, the model can be used to evaluate the impacts that BTS establishment at an additional site and that creation of a new source of snakes would have. The use of qualitative inputs allows the model to be adapted by substituting data on other invasive species or transportation systems.